2022
DOI: 10.1007/s11663-022-02445-1
|View full text |Cite
|
Sign up to set email alerts
|

On the Phosphorus Evaporation from Liquid Silicon by Knudsen Effusion Mass Spectrometry

Abstract: Silicon refining for solar applications is intensively on demand, and removal of phosphorus from Si is one of the most challenging steps. Evaporation of P from liquid Si in a vacuum refining process is the most efficient method for P removal from Si, and this research deals with the insight mechanisms of P evaporation from liquid Si. In this research, the gaseous species evaporating from the dilute liquid solutions of phosphorus in silicon were studied experimentally, and it was shown that phosphorus evaporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 71 publications
(110 reference statements)
0
1
0
Order By: Relevance
“…Upon increasing the pull-down speed, a large amount of P was enriched at the top of the sample, and more P diffused to the surface of the silicon melt under the action of an electromagnetic force. Hoseinpur A [25] et al used electromagnetic induction heating to stir molten silicon, which accelerated the diffusion of impurities in the silicon melt and obtained a large mass transfer coe cient. According to the mathematical model of phosphorus removal by vacuum directional solidi cation, Zhang [26] et al found that the segregation on the upper surface of silicon melt during this process concentrated phosphorus and facilitated phosphorus volatilization.…”
Section: Effects Of Different Pull-down Speeds On Al and P Distributionsmentioning
confidence: 99%
“…Upon increasing the pull-down speed, a large amount of P was enriched at the top of the sample, and more P diffused to the surface of the silicon melt under the action of an electromagnetic force. Hoseinpur A [25] et al used electromagnetic induction heating to stir molten silicon, which accelerated the diffusion of impurities in the silicon melt and obtained a large mass transfer coe cient. According to the mathematical model of phosphorus removal by vacuum directional solidi cation, Zhang [26] et al found that the segregation on the upper surface of silicon melt during this process concentrated phosphorus and facilitated phosphorus volatilization.…”
Section: Effects Of Different Pull-down Speeds On Al and P Distributionsmentioning
confidence: 99%